Peran Guru Sejarah dalam Menanamkan Karakter Cinta Tanah Air pada Peserta Didik Kelas X SMK Negeri 3 Pontianak - Hadri, Hadri; Sulistyarini, Sulistyarini; Mirzachaerulsyah, Edwin (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to understand the “role of History Teachers in Instilling Love for the Homeland in 10th-grade students at SMK Negeri 3 Pontianak.” The research method used is qualitative research in the form of descriptive research. The data sources for this study are history teachers and 10th-grad.e students. Data collection techniques include observation, interviews, and documentation, usingobservation guidelines, interview guidelines, and documentation tools as data collection instruments. The data analysis technique used in this research is qualitative descriptive analysis. The results of the study indicate that history teachers play their role in instilling a love for the homeland character in 10th-grade students at SMK Negeri 3 Pontianak through three efforts: utilizing the potential within SMK Negeri 3 Pontianak, implementing the school environment, and history teaching. History teachers fulfill their role effectively as mentors, educators, bridges between generations, seekers, counselors, creativity stimulants, and authorities. However, they face challenges, including students lack of awareness in participating in history lessons, insufficient use of facilities and infrastructure, a shortage of textbooks and adequate reference sources, and the school environment.